Identification and Profiling of microRNAs Expressed in Elongating Cotton Fibers Using Small RNA Deep Sequencing - Wang, Yanmei; Ding, Yan; Liu, Jin-Yuan (Frontiers in Plant Science, 2016)
Plant microRNAs (miRNAs) have been shown to play essential roles in the regulation of gene expression. In this study, small RNA deep sequencing was applied to explore novel miRNAs expressed in elongating cotton fibers. A total of 46 novel and 96 known miRNAs, primarily derived from the corresponding specific loci in genome of Gossypium arboretum, were identified. 64 miRNAs were shown to be differentially expressed during the fiber elongation process; 16 were predicted to be novel miRNAs while the remaining 48 belong to known miRNA families. Furthermore, RLM-5′ RACE (RNA ligase-mediated rapid amplification of 5’-cDNA ends) experiments identified the targets of 8 important miRNAs, and the expression levels of these target genes were confirmed to be negatively correlated with the expression patterns of their corresponding miRNAs. We propose a potential functional network mediated through these 8 miRNAs to illustrate their important functions in fiber elongation. Our study provides novel insights into the dynamic profiles of these miRNAs and a basis for investigating the regulatory mechanisms involved in the elongation of cotton fibers.